Gothenburg Papyrus 21 and the Coptic Version of the Letter to Abgar - Youtie, Herbert C. (Harvard theological review, 1931)
In the last number of the Harvard Theological Review I gave what I believe to be a definitive identification of the Gothenburg Papyrus 21. By way of demonstration I reproduced the text of the papyrus as reported by Frisk, with textual corrections and illustrative restorations of my own. I appended to the text a discussion in which I sought to establish its relations to other Greek versions of the Letter to Abgar. In my desire to bring to the attention of scholars a new Greek version of the Letter, the text of which presents remarkable departures from the traditional Eusebian version, my examination was restricted to the better known Greek sources. A subsequent examination of four additional Greek specimens of the Letter and of all the copies of the Coptic version, while necessitating no essential modification of my conclusions, has revealed in the Gothenburg papyrus important textual filiations which I did not then suspect.